EVALUATION OF PREVENTION OF MOTHER TO CHILD TRANSMISSION (PMTCT) IMPLEMENTATION IN YOGYAKARTA, INDONESIA: A 2023 ASSESSMENT (Proceedings of the Global Public Health Conference, 2025)
The Prevention of Mother-to-Child Transmission (PMTCT) program is essential for reducing new HIV infections. This study evaluated PMTCT implementation in Yogyakarta, Indonesia, in 2023 using a descriptive qualitative approach and the CIPPO model (Context, Input, Process, Product, Outcome). Data were gathered through interviews with stakeholders from the Provincial and District Health Offices, Community Health Centers, and hospitals. The results showed that PMTCT has been integrated into antenatal care, including HIV testing, referrals, labor management, newborn prophylaxis, breastfeeding support, and follow-up for HIV-positive mothers. Community education efforts helped reduce HIV stigma. However, challenges such as the absence of routine HIV testing in pre-marital medical exams, unplanned pregnancies, and the high mobility of pregnant women hinder case detection and monitoring. While implementation aligns with health regulations, improvements are needed to strengthen collaboration across sectors and with NGOs. This study highlights key areas for enhancing PMTCT services and contributes practical insights for achieving the goal of zero new HIV infections by 2030. Addressing identified barriers and leveraging existing strengths can lead to more comprehensive and equitable HIV prevention strategies in maternal and child health services.
Keywords: Adolescents; HIV Prevention; Pregnant women; PMTCT